Access to information in qualitative research. A matter of Care - de la Cuesta Benjumea, Carmen (Investigación y Educación en Enfermería, 2014)
In this article attention is focused on access to data; a process that tends to be taken for granted and which in practice takes time and energy from the person who investigates. Access implies a process of contacting key people in institutions; negotiating with them, being invited to obtain data, achieving formal permission, and – finally – constructing relationships with the participants. Access to data is negotiated, trust is constructed in relationships with study participants, and data is obtained. All this constitutes an interactive process in which the person who investigates is revealed as an instrument in obtaining the data. Thus, the appearance, manners, and the way of being of the person who investigates will facilitate access to broad and detailed information. Key words: qualitative research; data collection; ethics, research. How to cite this article: de la Cuesta C. Access to information in qualitative research. A matter of care. Invest Educ Enferm. 2014; 32(3): ____.